Monitoring Sistem Otomatisasi Hidroponik Berbasis Mobile - Hariono, Tholib; Fajriyah, Lailatul Fitri (Exact Papers in Compilation (EPiC), 2021)
Hydroponic farming systems have been widely applied in agriculture. The use of technology for automatic hydroponic systems is also being developed. The automated hydroponic system can automatically control the nutrient content in the water, which is the main element in the hydroponic farming system. In addition, control can also be carried out for water pH levels, water temperature, which is also essential to consider in a hydroponic planting system. Although the automatic hydroponic system can work independently, remote monitoring is needed to determine whether the automation system is working correctly or not. This research develops an automated hydroponic system on the side of mobile-based data monitoring. Through the development of a mobile-based monitoring system, the data for each sensor can be easily identified. The monitoring system can also find out whether the sensors in the automatic hydroponic system are working well or not. The method in software development uses the waterfall, while the manufacture of mobile applications uses framework 7. The results of this study are an Android-based mobile application that functions to monitor the condition of hydroponic plants. This application is connected to Arduino devices on hydroponics via cloud service.